2017
DOI: 10.3390/nano7030068
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Hybrid Nanosorbents for the Uptake of Paraquat from Water

Abstract: Although paraquat has been banned in European countries, this herbicide is still used all over the world, thanks to its low-cost, high-efficiency, and fast action. Because paraquat is highly toxic to humans and animals, there is interest in mitigating the consequences of its use, namely by implementing removal procedures capable of curbing its environmental and health risks. This research describes new magnetic nanosorbents composed of magnetite cores functionalized with bio-hybrid siliceous shells, that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 79 publications
(97 reference statements)
1
31
0
Order By: Relevance
“…Magnetic nanosorbents offer the great advantage of allowing fast recovery by employing magnetic separation technologies. A number of nanosorbents comprising magnetite nanoparticles have been reported by our laboratories, which include core/shell nanoparticles for the removal of heavy metal ions [18] and magnetic bionanocomposites for the removal of organic pollutants [19]. The successful implementation of magnetic nanosorbents depends, among other factors, on their efficiency for the selective uptake of pollutants, which requires further developments concerning the type of surface chemistry involved.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Magnetic nanosorbents offer the great advantage of allowing fast recovery by employing magnetic separation technologies. A number of nanosorbents comprising magnetite nanoparticles have been reported by our laboratories, which include core/shell nanoparticles for the removal of heavy metal ions [18] and magnetic bionanocomposites for the removal of organic pollutants [19]. The successful implementation of magnetic nanosorbents depends, among other factors, on their efficiency for the selective uptake of pollutants, which requires further developments concerning the type of surface chemistry involved.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…This strategy offers a convenient method to develop further studies envisaging the optimization of the substrate performance by adsorbing the magnetic particles with Au colloidal NPs with distinct SERS activity. The focus of this research was mainly to demonstrate the potential of such substrates for PG detection using the SERS effect, although there is potential for using the magneto-plasmonic properties of such materials in other water remediation processes [59,60]. For example, multifunctional nanosorbents combining magnetic and plasmonic components can be explored for the removal and laboratorial detection of a certain analyte or for monitoring a water purification process.…”
Section: Discussionmentioning
confidence: 99%
“…Also carbon‐based Fe 3 O 4 adsorbents were investigated for removal of cationic dyes from aqueous solution, such as methylene blue (MB), neutral red, fuchsine and cresyl blue , . Surface coatings made of biopolymers have also been used to functionalize Fe 3 O 4 NPs in order to remove organic compounds dissolved in water , . In these adsorbents, free side chain groups of biopolymers are available for chemical interactions with molecular contaminants.…”
Section: Magnetic Nanosorbentsmentioning
confidence: 99%
“…In these adsorbents, free side chain groups of biopolymers are available for chemical interactions with molecular contaminants. Several studies have demonstrated that magnetic‐polymer nanocomposites are promising for the uptake of organic dyes and heavy metal ions . For example, poly(c‐glutamic acid) coated iron oxide NPs (PGA‐MNPs) have been explored as adsorbents for methylene blue .…”
Section: Magnetic Nanosorbentsmentioning
confidence: 99%